Implementation of Poverty Reduction Policy Program Hope Family (PKH) in Bone Regency - Hamzah, Firman (Universitas Negeri Makassar, 2022)
This study aims to determine the implementation of the Poverty Reduction Policy for the Family Hope Program (PKH) in Bone Regency, especially in the health sector. This type of research is descriptive research with a qualitative approach. The data collection technique used in this study was through observation (observation), interviews, and documentation with the key informant of the head of the Social Service Office of Bone Regency using the qualitative interactive model data analysis technique from Miles Hubarman and Saldana. The results of this study indicate that the implementation of the Poverty Reduction Policy for the Family Hope Program (PKH), The Family Hope Program (PKH) in the health sector in Bone Regency has been implemented quite well, judging from the dimensions that there is sufficient time available, namely according to the schedule and cycle that has been set in implementing PKH in the health sector in Bone Regency. The implementation of the PKH program is of course realized by the existence of a clear cycle of the flow of assistance to the local community.